Penerapan Aplikasi Sehati Terhadap Peningkatan Pengetahuan Kesehatan Reproduksi Remaja pada Siswa/i SMA NU Kota Palembang - Herawati Jaya; Intan Kumalasari (Jurnal Kesehatan Komunitas, 2022)
To increase the knowledge and the adolescent’s manner about their reproductive health can do by giving them an education by using an application via android/IOS. On this application, we can share with them an education about their reproductive health. The purpose of this research is to know how is the impact of this application on the knowledge improvement of reproductive health in Negeri Umum senior high school students in Palembang. This study used a pre-experimental design method with the type of one group pretest-posttest (single group initial test and final test). The method to create a sample of this research is using Simple Random Sampling that has 70 samples and it comes from 10-grade students, 11-grade students, and 12-grade students. The results by applying Wilcoxon Signed Rank Test show a significant number of the sixth variable (α <0,005) which all the variables about  Show a resulting p-value of 0,000. Based on the statistical analysis above, it can be concluded that there is a significant difference in using the Sehati application on increasing senior high school Negeri Umum Palembang’s student knowledge about reproductive health.